Heaping and secondary flows in sheared granular materials - Börzsönyi, Tamás; Fischer, David; Schiochet Nasato, Daniel; Pöschel, Thorsten; Stannarius, Ralf (New Journal of Physics, 2016)
Cylindrical containers with a rotating bottom disk (so-called split-bottom geometry) are well established devices to shear granular materials in a continuous way, and to generate well-defined localized shear bands in the granular bed. When material composed of shape-anisotropic grains is sheared in such a container, a secondary flow is generated that leads to the formation of a considerable heap of material near the rotation center. We demonstrate that this effect can be found not only with prolate grains, as shown in a previous study, but also for oblate particle shapes. In addition, the quantitative influence of geometric and dynamic parameters is studied systematically. It is shown that the fill height of the container has considerable influence on the time scale for heap formation, but much less effect on the heap height. Results of numerical simulations agree with the experimental findings and provide insight in the particle dynamics.